Agroforestry Practices in Hill Farming of Sikkim - , Patiram; Bhadauria, S. B. S.; Upadhyaya, R. C. (Indian Forester, 1996)
The traditional agricultural systems in the different climatic zones of sikkim have evolved over a long time scale within the historic period. The existing current practices of agroforestry in hill agriculture include large cardamom a plantation crop combination, bamboos all along the stream banks and drainage channel, fodder trees and grasses on terrace risers and wasteland, agri-horti system especially mandarin and intercrops and homestead gardening etc. Practically most of the adopted agroforestry land use systems require neither most costly external inputs nor complex technology. The traditional hill agriculture including horticulture, forestry and livestock together meet the demands of the local people food, fodder, fuel, fertilizer, fibre; timber, medicinal and commodity crops, and also giving some economic return. The indigenous trees are given to increase the over all Productivity on long term basis.